Attitudes of young Singaporeans towards music piracy - Aw, Mei Yi (2008)
Music piracy needs immediate addressing due to advances in digital copying technologies. Hence, this paper proposes a model of potential determinants of the intention to download music at illegitimate websites and to burn CD, so as to suggest more effective anti-piracy solutions. The value individuals place on music, their awareness and support towards local anti-piracy campaigns are also investigated.